TO PLAY OR NOT TO PLAY? A CASE STUDY OF TEACHERS’ CONFIDENCE AND PERCEPTION WITH REGARD TO DIGITAL GAMES AT SCHOOL - Fedela Feldia Loperfido; Anna Dipace; Alessia Scarinci (Italian Journal of Educational Technology, 2019)
Teachers’ perception of the use of games for learning is a crucial aspect for the creation of Game-Based Learning experiences. At the same time, solid research on this point is still lacking. For this reason, this study analyses the confidence, knowledge and attitudes of teachers in an Italian school in the context of the use of digital games in teaching activities. To this end, we administered both the TPACK-G and ADGBL questionnaires, and conducted two focus groups. Descriptive statistics were used to analyse the results of the questionnaires, and qualitative content analysis was used to analyse the focus group discussions. Results show that the teachers’ perception is characterised by several not necessarily interrelated aspects: they make sense of game based learning by comparing it with traditional didactics; they usually organise teaching activities with games to reach traditional goals (e.g. summative evaluation, individual study, etc.); and finally, they seem to be in a transitionary phase during which games have not yet been internalised as a resource for innovation.